2012
DOI: 10.4490/algae.2012.27.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GeO2on embryo development and photosynthesis in Fucus vesiculosus (Phaeophyceae)

Abstract: Germanium dioxide (GeO 2 ) has been used for many years in the cultivation of red and green algae as a means of controlling the growth of diatoms. Brown algae are sensitive to GeO 2 , however, the basis of this sensitivity has not been characterized. Here we use embryos of Fucus vesiculosus to investigate morphological and physiological impacts of GeO 2 toxicity. Morphometric features of embryos were measured microscopically, and physiological features were determined using pulse amplitude modulated (PAM) fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The apparently universal applicability of Ge-capping can be used to investigate the wider role of silicon in biology [ 4 ], even in apparently non-silicifying organisms or cryptic silicifiers [ 22 ]. For example, Ge causes cell division anomalies in Fucus vesiculosus embryos, despite this species having no known requirement for Si [ 48 ]. Interestingly, Ge also exerts toxic effects on mammalian kidneys [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The apparently universal applicability of Ge-capping can be used to investigate the wider role of silicon in biology [ 4 ], even in apparently non-silicifying organisms or cryptic silicifiers [ 22 ]. For example, Ge causes cell division anomalies in Fucus vesiculosus embryos, despite this species having no known requirement for Si [ 48 ]. Interestingly, Ge also exerts toxic effects on mammalian kidneys [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…; Tarakhovskaya et al . ). Most previous experimental work was carried out by removing thalli from the field and doing experiments in a laboratory setting (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…We focus on diurnal changes in photosynthesis, and the effects of irradiance and desiccation experienced in situ on FPSII. Effective quantum yield can show photosynthetic activity according to previous light condition immediately, because effective quantum yield changes in a short time (Ralph et al 2002;Kim & Garbary 2009;Choi et al 2010;Kim et al 2011;Tarakhovskaya et al 2012). Most previous experimental work was carried out by removing thalli from the field and doing experiments in a laboratory setting (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, silica is not normally considered an essential element for the Phaeophyceae and can be omitted from culture medium with no apparent deleterious effects (McLachlan et al 1971). Secondly, Tarakhovskaya et al (2012) showed that GeO 2 interferes with growth and development in the phaeophyte Fucus vesiculosus leading to morphological abnormalities. The authors suggest that this action maybe due to Ge substituting for boron within various complexes, which is known to have deleterious effects in land plants (McIlrath and Skok 1966).…”
Section: Introductionmentioning
confidence: 98%